Changes in water vapor adsorption and water film thickness in clayey materials as a function of relative humidity - Lin, X. (2020)
The variation of water film is obtained from the analysis of interfacial forces, and then the total water content can be quantitatively subdivided into these three types of water for different RH values. The slit‐pore adsorption model was used with experimental measurements (water vapor adsorption and N2 physisorption) to quantify the amounts and interrelationships of these three different types of water to six clayey materials, namely three clay minerals (kaolinite, montmorillonite, and illite–smectite mixed layer) and three clay‐rich sediments from the Jianghan Plain in China. The main results are that (a) the volumes of water vapor adsorption are much greater than those of N2 adsorption except for kaolinite; (b) interlayer water largely dominates the growth of total water content in montmorillonite and results in a concentration of 0.090 ml g−1 at 95% RH; and (c) the minimum thickness of water film is calculated to be 0.23 nm, and the maximum value is one‐third of the pore width by considering the interfacial forces.